Are all heparins safe for on-pump heart surgery?. Issue 7 (2nd July 2016) - Azarnoush, Kasra; Pereira, Bruno; Lebreton, Aurelien; Zenut, Marie-Christine; Chenaf, Chouki; Vedat, Eljezi; Cosserant, Bernard; Bouvier, Damien; d'Ostrevy, Nicolas; Camilleri, Lionel
ABSTRACT: Background: Intravenous Panpharma heparin ® was used in all on-pump cardiac surgery in our heart-surgery department for a short period. This brand of heparin replaced the previous Choay heparin ® heparin supplied by the Sanofi-Aventis Laboratory. Unusual postoperative bleedings over this period prompted us to evaluate postoperative hemostasis by comparing these two heparins. Methods: We compared data from patients who had undergone on-pump cardiac surgery during Panpharma heparin ® period (group P, 257 patients) to those how received Choay heparin ® (group C, 194 patients). Results: Despite group P receiving a significantly lower dose of heparin (mean dose 21, 000 IU/CEC) compared to group C (mean dose 22, 000 IU/CEC) ( p  = 0.05), the number of surgical re-explorations needed to perfect postoperative hemostasis was significantly higher for group P (3.5% vs. 0) ( p  = 0.01). Heparin anti-Xa activity after surgery was higher in group P at postoperative h1 and h12 compared to group C, which explained reoperations for hemostasis. Conclusion: Despite standardization, variations remain regarding anticoagulant activity between different manufacturing processes and heparin preparations. Surgical teams need to be aware that the biological effects of different brands of heparin may not be as expected and could endanger a usually safe procedure, such as cardiac surgery.